Degraded land rehabilitation role of chomo grass (Brachiaria humidicola) and its socioeconomic importance; evidence from Western Ethiopia - Tamiru Chalchisa Geleto; Mulubrihan Bayisa Tulu (Brawijaya University, 2020)
In order to combat the problem of land degradation, a lot of efforts have been made since 1970s in Ethiopia. This study was conducted in Manasibu woreda of West Wollega zone to Degraded Land Rehabilitation role of chomo grass (Brachiaria humidicola) and it’s Socioeconomic Importance. Local farmers’ perception, major causes and management practice were also assessed. About 139 sample respondents were selected randomly from four purposively selected kebeles in the woreda. Interview schedule, focus group discussion, key informant interview and participatory observation were used to collect data from sample respondents. The result of the study indicates that local peoples are using chomo grass for various purposes. Particularly they use for forage, for sale, more importantly for environmental rehabilitation, and making of some home utensils among the other. They are selling both seed and grass and earn a good income. Chomo grass was their first and last choice. Accordingly, chomo grass was well introduced in the area. Thus the study concludes as chomo grass has curative values for communities’ number one problems; soil degradation. Accordingly, the efforts in expanding the grass in effective land management should be scaled up to other areas having a similar situation.